In vitro study of electrodeposited fluoridated hydroxyapatite coating on G-II titanium with a nanostructured TiO2 interlayer. (4th April 2017) - Lin, Jin-Shyong; Tsai, Tzung-Bau; Say, Wen-Ching; Chiu, Chun; Chen, Shih-Hsun
Abstract: Titanium and its alloys have been widely used as orthopedic and dental implants for several decades due to their superior mechanical properties, corrosion resistance and biocompatibility. Recently, many researches revealed that the hydroxyapatite coatings on biomedical materials can further improve their biocompatibility and bioactivity. However, hydroxyapatite coatings are easily decomposed, weakening the bonding between implants and bone tissues and resulting in a high dissolution rate in the biological environment. Prolonging the lifetime of hydroxyapatite in implants is valuable for improving postoperative quality. Hydroxyapatite is the primary inorganic component of bones and teeth. A suitable amount of fluoride ions would be beneficial for the formation of fluoridated hydroxyapatite, which can enhance bone-cell response and the acid resistance of enamel. In this study, G-II titanium substrate was anodized to form a TiO2 interlayer with a nanotube structure. An electrolyte composed of fluoride, calcium and phosphorus ions was prepared for electroplating fluoridated hydroxyapatite (FHA) coatings onto anodized G-II titanium substrates at a constant voltage. The obtained coatings were examined for their microstructure, mechanical properties; moreover, the changes of apatite structure, surface morphology and corrosion resistance were further investigated after immersion in simulated body fluid (SBF) for a number of weeks. The results show that FHA coatings have a higher surface roughness and hardness than plain hydroxyapatite. After immersion in SBF, the FHA coatings induced the nucleation and growth of apatite on the surface and increased their crystallinity. In a potentiodynamic polarization test, FHA coatings exhibited a better anti-corrosion ability than bare G-II titanium substrate in SBF. Additionally, the anodized TiO2 nanotube improved the adhesion and corrosion resistance of FHA as well.